Magnetism : A Very Short Introduction - Blundell, Stephen (Oxford Oxford University Press, 2012)
What is that strange and mysterious force that pulls one magnet towards another, yet seems to operate through empty space? This is the elusive force of magnetism. In this Very Short Introduction Stephen J. Blundell considers early theories of magnetism, the discovery that Earth is a magnet, and the importance of magnetism in modern technology.
Include Illustrations, Appendix and Index.
A Very Short Introduction.
Keywords: Magnetism